الترجمة وأثرها في المثاقفة بين الأنا والآخر - شادلي، عمر Shadli, Omar; بن يمينة، رشيد (مركز جيل البحث العلمي, 2016)
تعدّ الترجمة آلية من آليات التواصل الحضاري،وسبيل من سبل نقل المعارف،وأسّ من أسس المثاقفة بين الأمم والشعوب ،ولولاها لبقي الإنسان أحادي المعرفة والفكر،ولما استطاع أن يطّلع اطلاعا بانوراميا على الآخر L’autre وبقي خالي الوفاض من معرفته،ولقد كان لها إسهام كبير في المثاقفة L’acculturation بين الأنا والآخر، وهذا ما دفعنا للتساؤل عن دور الترجمة في نقل المعارف وتبادلها بين الأنا المتوسطية والآخر الممثّل من طرف الدول الأروبية . ونحن في ورقتنا البحثية نسعى سعيا حثيثا للإجابة عن هذا التساؤل عن طريق تحديد ماهية الترجمة وعن ابعادها ،وعن دورها الفعال في احياء التبادل الثقافي بين الأنا والآخر في مختلف العلوم وشتى المجالات،وعن ترسيخها للهوية دون إقصاء الذات أو تهميش الآخر
THE Sejet: The forms of cultural communication The influence of translation in the culturing enter ego and addition. This research focuses on marked right to: a form of cultural interaction and the impact of the conversion on the acculturation between the self and the other .. Who treated a statement on the importance of translation in communication rounded distances between peoples, which is acculturation resulting from a translator of the most important current cultural, intellectual, language and humanity despite the multiplicity of languages however, he continues prevailed among peoples. When these media have become civilized - cultural bridge of communication or cognitive - and the window on to what people on the other, as the art of arts of the current intellectual and cultural production, and continue to be the medium to convey knowledge or cognitive channel the dialogue between peoples because of their active role to highlight the cognitive area and lay the foundation, and to expand the circle of access to the culture of the other, being a cultural asset . The media for this intellectual current cultural contexts are inside, some ideologies. By imposing the idea of domination between East and West and the imposition of hegemony over the peoples of the third world was like us, have a look at all of the ego and the other party saw from first on the basis of authoritarianism; while the other believes that the ego seen look denigration. And it was with the idea of how the other receivers. So we can win in the last of the spirit of the big idea Alhawwar.oha culture that combines the two extremes
Keywords: الترجمة -- المثاقفة -- التبادل الثقافى -- التواصل الحضارى